(untitled) (Publicaciones en Ciencias y Tecnología, 2024)
Plastics negatively cause internal or external damage to marine species and public health problems. In addition, they contribute to the deterioration of the aquatic system since they transport other pollutants such as endocrine disruptors, and flame retardants, among others. This research proposes a systematic review of the literature from the last 5 years to examine the bioremediation methods proposed for plastic pollution. Degradative methods (microorganisms, fungi, and algae) represent 45% of the articles used in the systematic review. Other direct remediation methods identified are advanced oxidative processes (17%) and endothermic processes (14%). Although there are applicable methods such as pyrolysis and thermodegradation, they have disadvantages such as energy cost, low product quality, and the risk of releasing microplastics into the environment. The scaling between the dimensions of the laboratory and the real needs constitutes challenges for the future applications of these methods.